ARAHAN KEBIJAKAN MITIGASI BENCANA GUNUNGAPI KABA DI KABUPATEN REJANG LEBONG PROVINSI BENGKULU - M. Iqbal Liayong Pratama; Hendra -; Hamengkubuwono -; Hary Febrianto (Jurnal Azimut, 2019)
This research is based on the Government’s lack of concern for the risk of Kaba Volcano eruption. Lack of preparedness of disasters, socialization for disaster mitigation, availability of the evacuation routes, or early warning systems in Kaba Volcano. On the other hand, with disaster preparedness, the damage and casualty figures can be minimized. The purpose of this study is to formulate the mitigation priority direction of Kaba Volcano eruption. Data collecting used interviews, observation and collecting relevant information. Then the data are grouped according to the danger levels criteria, the vulnerability, and the risks. Data processed by scoring and analyzing with AHP (Analytical Hierarchy Process). The results show that the direction of Bukit Kaba eruption mitigation priorities as follows: measured and periodic training and disaster simulation aspect is (0.832), coordination and collaboration in anticipating disasters is (0.813), human resources preparation is (0.801), evacuation route and site is (0.799), and the early warning system is (0.795).